Inventory Control Process Using MRP (Material Requirement Planning) In Production Planning at PT. Dae Young Apex Ind - Renaldi, Renaldi; Amarudin, Hamdan (Proceeding International Pelita Bangsa, 2023)
In production planning, the company wants to make efficiency, especially on inventory stock or stock availability which must be controlled so that storage costs are not too long and the control process in purchasing raw materials can be adjusted as needed. The Matrial Requirement Planning (MRP) method is a method for planning raw material supplies with the aim of calculating the costs to be used, and the results of calculations using the MRP method, Lot For Lot (LOL) is the safest method to use because it costs a small amount of Rp. 111,276,000 with an ordering schedule for 1 period before it is needed, from other methods, namely EOQ and POQ. And the Forecasting Method is a method used to calculate needs in the following month with the aim of ensuring that the raw materials to be ordered can be adjusted, the forecasting method used is the Weighted Moving Average (WMA) because the MAPE calculation results have a small percentage of 6.94%, with a small percentage of safe calculation data to carry out the forecasting process in raw material planning